«Grey» Importation over the Russian-Chinese Border: What’s New? - Татьяна Николаевна Журавская (Journal of Economic Sociology, 2011)
The research aims at describing mechanisms and practices of «grey» importation of consumer goods over the Russian-Chinese border. It also demonstrates significant changes which happened over the last 10 years. The city of Blagoveshchensk (Amur region) serves as a case studied. Data covers in-depth interviews, observations, information from the website «Amur.info» and relevant legislation. «Grey» importation and shuttle trade are discussed from the standpoint of the new institutional economics and networks perspectives. The comparison of early and late 2000s business practices shows that applied «grey» business schemes are flexible and universal. In addition, there are important shifts in actors’ status, role of Customs office and goods quality.